A: Studi Banding Pelayanan Pangan Rumah Sakit Islam Negeri dan Swasta di Makassar - Yusma Indah Jayadi; Rezki Nurfatmi; A. Syamsiah Adha; Sukfitrianty Syahrir; Dian Ihwana Ansyar; Ichsanul Ahkam (State Islamic University of Sunan Ampel, 2023)
Institutional and industrial food delivery is an integrated program consisting of planning, procuring, storing, processing foodstuffs, and serving or serving food on a large scale. This feeding activity must be guided by the PGRS to ensure quality food so that patients can accelerate the healing process. The implementation of institutional food even though it is guided by PGRS, in fact in the field there are differences in its application, especially in hospital nutrition installations. This study aims to compare the management of food organizations and services in the nutrition installation of Islamic hospitals and general hospitals. This research is a type of qualitative research in May 2022 with a demonology approach, namely describing the implementation of management in food delivery activities at the Nutrition Installation of Faisal Islamic Hospital and Pelamonia Hospital. The subjects in this study were the head of the hospital, processing personnel, nutritionists, waiters and patients' families. The study of data collection through in-depth interviews using a list of questions. Differences in the implementation of management in food delivery activities at the Nutrition Installation of Faisal Islamic Hospital and Pelamonia Hospital which include good kitchen requirements, the needs of officers in nutrition installations, planning for food needs, procurement of foodstuffs, officers who process foodstuffs, prerequisites for processing foodstuffs, and food distribution officers. : It is expected for the Faisal Islamic Hospital and Pelamonia Hospital to evaluate by the Minister of Health of the Republic of Indonesia No. 73 of 2013 concerning Guidelines for Hospital Nutrition Services.